2005
DOI: 10.1016/j.seizure.2005.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour problems in children and adolescents with seizure disorder: associations and risk factors

Abstract: Psychopathology reflected a complex interaction of seizures, socio-demographic factors and treatment related variables, in accord with studies in industrialised countries. Clinicians should be sensitive to identifying psychopathology since this may lead to effective interventions for this group of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
5
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 24 publications
7
41
5
3
Order By: Relevance
“…17 A clinic-based study in India of children from an urban setting attending outpatient clinics with a diagnosis of epilepsy found that 54% had significant psychopathology on the CBCL. 16 In our study, the prevalence of behavioural disorders was higher. This difference is likely to be multifactorial and may be due to different study populations, rural versus urban settings, or more symptomatic epilepsy.…”
Section: Discussion Prevalence Of Behaviour Disorders In Children Witcontrasting
confidence: 38%
See 1 more Smart Citation
“…17 A clinic-based study in India of children from an urban setting attending outpatient clinics with a diagnosis of epilepsy found that 54% had significant psychopathology on the CBCL. 16 In our study, the prevalence of behavioural disorders was higher. This difference is likely to be multifactorial and may be due to different study populations, rural versus urban settings, or more symptomatic epilepsy.…”
Section: Discussion Prevalence Of Behaviour Disorders In Children Witcontrasting
confidence: 38%
“…Two studies from India found similar rates of behavioural (54%) and psychiatric disorders (23%) to those reported from high-income countries. 16,17 There are only a few studies on behavioural disorders in children with epilepsy from Africa. A study of 102 Nigerian adolescents with epilepsy who were attending a neuropsychiatry outpatient clinic found that 31% had anxiety and 28% had depression.…”
mentioning
confidence: 99%
“…[22] Bu çalışma-nın aksine, Hindistan'dan bir çalışmada ise yüksek sosyoekonomik düzeydeki hastalarda daha fazla davranışsal sorunlar gözlendiği bildirilmiştir. [23] Nörobiyolojik risk faktörleri arasında epilepsi ile ilişkili faktörler üzerine odaklanılmıştır. Çocuk ve ergenlerde yapılan araştırmaların çoğunluğu nöbet tipi ile depresyon riski arasında belirgin bir ilişki olmadığını göstermiştir.…”
Section: Risk Faktörleriunclassified
“…Children who have experienced early trauma, such as neglect and physical and emotional abuse, present with characteristics meeting the criteria for autism (Nader, 2008). Children with early learning disabilities or medical complications such as seizures, ear infections, and birth defects, present with similar features of social withdrawal, repetitive behaviors, and limited speech (Ceci, 1986;Datta et al, 2005;Ellis, Schnoes, & Roberts, 2010).…”
Section: Differentiating the Diagnosismentioning
confidence: 99%